The Impact of Organizational Citizenship Behaviour, Knowledge Management, and Work Environment on Employee Performance in Manufacturing Firms - Herliyanti, Rika Putri; Kurniawan, Ignatius Soni; Lysander, Mohammad Ahyar Syafwan (Manunggal Halim Jaya, 2025)
Improving employee performance in manufacturing companies can help companies achieve greater profits. Employee performance is based on factors such as organizational citizenship behavior, knowledge management, and physical work environment. This study uses a quantitative approach to analyze the influence of these three factors on employee performance at CV—Lotus Glove Berbah, Yogyakarta, involving 80 employees, and a multiple linear regression analysis method. The results showed that organizational citizenship behavior and knowledge management partially have a positive but insignificant influence on employee performance. In contrast, the physical work environment positively and significantly affects employee performance. Simultaneous tests show that the three variables positively and significantly affect employee performance. The R-square value of 0.537 indicates that organizational citizenship behavior, knowledge management, and physical work environment simultaneously explain 53.7% of the variability in employee performance at CV. Lotus Glove Berbah. Meanwhile, the rest is influenced by other factors beyond the scope of this study.